2018
DOI: 10.1016/j.cemconres.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable ashes as Supplementary Cementitious Materials

Abstract: Approximately 140 billion metric tons of biomass are produced every year in the world from agriculture. The ashes resulting from firing agricultural wastes such as rice husk, sugar cane and others can be used as Supplementary Cementitious Materials (SCM). They can be mixed with lime alone or in ternary mixtures with Portland cement and lime. If fired at temperatures around 600-700 o C the agricultural ashes exhibit good reactivity. Despite extensive research work carried out on the use of agricultural ashes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 35 publications
1
50
0
2
Order By: Relevance
“…The amorphous mineralogical character and high silicon dioxide (SiO 2 ) content of these materials are usually responsible for controlling the stability and the development of high strength in the end product (Shafiq et al, 2018). In addition, the trend of using biowastes from fuel sources in concrete, such as wheat straw ash, palm oil fuel ash, rice husk ash, and sugar cane bagasse ash, is increasing significantly in those countries that produce large amounts of these wastes that cause severe environmental issues if dumped in open fields (Binici et al, 2008;Martirena and Monzó, 2018). Previous studies show that sugar cane bagasse ash, which is a byproduct of the sugar cane industry, can be an effective material to be used in producing sustainable concrete (Ganesan et al, 2007;Aigbodion et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous mineralogical character and high silicon dioxide (SiO 2 ) content of these materials are usually responsible for controlling the stability and the development of high strength in the end product (Shafiq et al, 2018). In addition, the trend of using biowastes from fuel sources in concrete, such as wheat straw ash, palm oil fuel ash, rice husk ash, and sugar cane bagasse ash, is increasing significantly in those countries that produce large amounts of these wastes that cause severe environmental issues if dumped in open fields (Binici et al, 2008;Martirena and Monzó, 2018). Previous studies show that sugar cane bagasse ash, which is a byproduct of the sugar cane industry, can be an effective material to be used in producing sustainable concrete (Ganesan et al, 2007;Aigbodion et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reported advantages in durability of cement-based composites containing SCBA, an evaluation of long-term durability of composites containing SCBA is necessary [38][39]. The performance of steel embedded in composites containing SCBA against corrosion must be addressed.…”
Section: Durability Properties Of Scbacmentioning
confidence: 99%
“…Approximately 140 billion metric tons of biomass are produced every year in the world from agriculture. For each ton of processed sugarcane, there are 270 kg of bagasse [5,[9][10][11][12]. In India, for instance, it is reported that about 600 Mt/year of rice husk have been generated from agricultural sources alone.…”
Section: Introductionmentioning
confidence: 99%